2006
DOI: 10.1097/01.scs.0000231628.10511.bb
|View full text |Cite
|
Sign up to set email alerts
|

Various Applications of Chondrocutaneous Composite Grafts in Secondary Cleft Lip Nose Patients

Abstract: Composite chondrocutaneous grafts were applied to 12 patients in various forms to repair the columellar deficit, to form the nasal tubercle and nostril sill in cleft lip nose patients. Cleft lip-nose deformity patients with alar cartilage hypoplasia, obtuse angulation of the medial and lateral crura and the resulting plica vestibularis, internal nasal valve problems associated with the weakness of upper lateral cartilages are included in this study and composite conchal cartilage grafts are utilized to achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Driscoll and Baker (2001) claimed that reconstruction for most patients with nasal alar defects can achieve a highly aesthetic and functional result through the use of a multistaged procedure using free cartilage grafts and vascularized flaps. Ayhan et al (2006) and Joseph and Richard (2008) reported that mobilization, repositioning, and transposing flaps or grafts to the deficient inner surfaces of the vestibule, columella, and upper lateral cartilages form the basis of secondary nasal deformity reconstruction. However, there are only a few previous reports (Millard, 1976;Miyamoto et al, 2007) regarding the evaluation and treatment of alar base depression in nasal deformity secondary to unilateral cleft lip.…”
Section: Discussionmentioning
confidence: 99%
“…Driscoll and Baker (2001) claimed that reconstruction for most patients with nasal alar defects can achieve a highly aesthetic and functional result through the use of a multistaged procedure using free cartilage grafts and vascularized flaps. Ayhan et al (2006) and Joseph and Richard (2008) reported that mobilization, repositioning, and transposing flaps or grafts to the deficient inner surfaces of the vestibule, columella, and upper lateral cartilages form the basis of secondary nasal deformity reconstruction. However, there are only a few previous reports (Millard, 1976;Miyamoto et al, 2007) regarding the evaluation and treatment of alar base depression in nasal deformity secondary to unilateral cleft lip.…”
Section: Discussionmentioning
confidence: 99%
“…Ayhan et al published a series of cases where composite conchal cartilage was used in various forms to repair columellar deficit, to form nasal tubercle and nostril sill in cleft lip nasal deformity patients and concluded that conchal cartilage achieved symmetric and functional results. [ 21 ] Turkaslan et al described a technique to place a cartilage graft at the posterior dome area after the release of cleft side ala from vestibular mucosa and skin to elevate the ala depression and tip projection. [ 22 ] Septal cartilage was used in presented case and was satisfactory and a second donor site morbidity was avoided.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Ayhan et al published a series of 12 cases in which composite chondrocutaneous grafts were applied in various forms to repair the columellar deficit and to form the nasal tubercle and nostril sill in cleft lip nose patients. 10 The authors felt that composite conchal cartilage grafts achieved a symmetrical and functional result. These techniques are similar in nature to previously described composite grafting techniques and may be appropriate on a case by case basis.…”
Section: Other Techniques In Secondary Cleft Rhinoplastymentioning
confidence: 99%